SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT MULUT PADA MANUSIA BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract : Any human with mouth disease would bea high coriousity for them selves to know what are the diagnose of they disease. They often shy or do not have any time going to the doctor or expert person. Researcher Aim to design a software system that helps the human to recognize and diagnose what are they disesase on mouth. Software was build using the PHP programming language and tools used are Notepad++ as a program listings editor, XAMPP as a web server, and MySQL as a database uses. The results of the software is expected to facilitate the doctor or the whole human with mouth disease The resulting software is still needed development for the future, so expected become a more perfectly life cycle study. Keywords : System, Information, Expert System, Patology